Identification of prognostic factors in childhood T‐cell acute lymphoblastic leukemia: Results from DFCI ALL Consortium Protocols 05‐001 and 11‐001. Issue 1 (7th October 2020) - Burns, Melissa A.; Place, Andrew E.; Stevenson, Kristen E.; Gutiérrez, Alejandro; Forrest, Suzanne; Pikman, Yana; Vrooman, Lynda M.; Harris, Marian H.; Weinberg, Olga K.; Hunt, Sarah K.; O'Brien, Jane E.; Asselin, Barbara L.; et al.
Abstract: Background/objectives: While outcomes for pediatric T‐cell acute lymphoblastic leukemia (T‐ALL) are favorable, there are few widely accepted prognostic factors, limiting the ability to risk stratify therapy. Design/methods: Dana‐Farber Cancer Institute (DFCI) Protocols 05‐001 and 11‐001 enrolled pediatric patients with newly diagnosed B‐ or T‐ALL from 2005 to 2011 and from 2012 to 2015, respectively. Protocol therapy was nearly identical for patients with T‐ALL (N = 123), who were all initially assigned to the high‐risk arm. End‐induction minimal residual disease (MRD) was assessed by reverse transcription polymerase chain reaction (RT‐PCR) or next‐generation sequencing (NGS), but was not used to modify postinduction therapy. Early T‐cell precursor (ETP) status was determined by flow cytometry. Cases with sufficient diagnostic DNA were retrospectively evaluated by targeted NGS of known genetic drivers of T‐ALL, including Notch, PI3K, and Ras pathway genes. Results: The 5‐year event‐free survival (EFS) and overall survival (OS) for patients with T‐ALL was 81% (95% CI, 73‐87%) and 90% (95% CI, 83‐94%), respectively. ETP phenotype was associated with failure to achieve complete remission, but not with inferior OS. Low end‐induction MRD (<10 −4 ) was associated with superior disease‐free survival (DFS). Pathogenic mutations of the PI3K pathway were mutually exclusive of ETP phenotype and were associated with inferior 5‐year DFS and OS. Conclusions: Together, our findings demonstrate that ETP phenotype, end‐induction MRD, and PI3K pathway mutation status are prognostically relevant in pediatric T‐ALL and should be considered for risk classification in future trials. DFCI Protocols 05‐001 and 11‐001 are registered at www.clinicaltrials.gov as NCT00165087 and NCT01574274, respectively.